Processo de otimização aplicada à análise de risco de investimento em geração de energia elétrica com fontes renováveis - Pinheiro Neto, Daywes (2017)
This work presents a methodology for multiobjective optimization applied to risk analysis of investment in electricity generation from renewable sources. Analysis of hydro (large-scale and small-scale), wind, and photovoltaic energy is carried out considering the economic profile and demand of the investor. The methodology of risk analysis applies the Monte Carlo method to generate synthetic time series of the random variables. The investment analysis approaches are made for individual sources and also for different portfolios, using detailed modeling for the cash flow. The proposed mathematical modeling of multiobjective optimization takes into account aspects of commercialization, legislation, taxation, financing, and the investor's demand. The results provide information of the generation potential, statistical indicators of the Net Present Value and Modified Internal Rate of Return, as well as the Pareto frontiers. Thus, the investor can choose the best portfolio with hydro, wind and photovoltaic energy which satisfies their demand characteristics and their financial risk profile. Therefore, this work offers a valuable tool to support decision making and to contribute with the electric sector development.